Draft Annual Plan 1980-81 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1980)
The outlay on the Annual Plan for 1979-80 included in the Budget is Rs. 450.00 crores. The outlay on the Annual Plan 1979-80; approved by the Planning Commission is Rs.421.50 crores subsequently, two contingencies arose in the State which necessitated a review of the current years plan. Firstly, because of the severe cyclone that affected the State, the State had to spend large amounts for providing relief to the cyclone victims. Secondly, as a result of the decision of the National Development Council certain scheme have been deleted from the list of Centrally Sponsored Schemes, and some schemes have been transferred to the category for which only 50$ Central assistance will be forthcoming. To provide for such of these schemes which are considered essential, suitable provision will have to be made in the State’s Annual Plan for 1979-80. Having regard to these contingencies, the allocations in the .plan for 1979-80 have been realigned without giving up the basic objectives of the plan for 1979-80.
Government of Andhra Pradesh
Finance and Planning Department Hyderabad
Keywords: Dairy Development; Community Development Programme and Panchayats; Food for Work Programme; Godavari Barrage Project; Other Major and Medium Irrigation; Power Andhra Pradesh State Electricity Board; Large and Medium Industries; Mines and Geology; Andhra Pradesh State Road Transport; Tourism; General Education Adult Education